Secondary English teacher education in the United States - Pasternak, Donna L.; Caughlan, Samantha; Hallman, Heidi L., 1976-; Renzi, Laura; Rush, Leslie S., 1962- (Reinventing teacher education., 2017)
"Identifying key areas of teacher education that cross countries and disciplines, this book provides the first extensive research-based insight into how secondary English teachers are prepared at institutions of higher education in the United States of America (US) since the last major study in 1995. In the two decades since then, English teacher education programs have developed in contextually dependent ways that often have been driven by institutional, economic, social and political considerations. In Part I, the authors provide an overview of their nationwide study of English teacher educators, which was conducted over a four-year period. They then analyze the context under which teacher educators currently prepare pre-service English teachers in the US. This enables teacher educators in other countries to make comparisons to their own unique historical and cultural settings. Part II offers an evaluation of the content, practices and skills being taught to future teachers of English in university-based teacher preparation programs in the US. It draws on evidence from case studies, course syllabi and focus group interviews to focuses on areas of instruction that resonate with teacher educators in countries where English is the dominant language of communication. These areas include: - standards and assessment; - teaching literacy to integrate reading and writing; - working with English language learners to address cultural and linguistic diversity; - new technologies in English education. This book will serve as a model for other secondary school disciplines worldwide to examine their own content, skills, and practices to ascertain the conditions under which teacher preparation occurs"--